Frank Capra and Elia Kazan, American outsiders - Yves Carlet (European Journal of American Studies)
Frank Capra and Elia Kazan both came to the United States as children. From immigrant stock, each experienced the effects of being looked down upon as outsiders to Anglo culture. Based on the two men’s autobiographical accounts, together with their films and biographical writings about them, this article examines the routes by which they sought entry into the dominant culture. This process would require the rejection, in each case, of part of his family heritage. It would lead to very different attitudes to ethnicity in their films: Kazan demonstrated interest in the subject, whereas Capra largely suppressed it. The article underlines other “covert dialogues” in the films directed by the two men. It shows that they most diverged over issues of sexuality and the later rediscovery of their ethnic roots.